Kelebihan dan Kekurangan Pemilu Serentak Indonesia: Studi Kasus Terhadap Kematian Anggota KPPS Pada Pemilu Serentak 2019 - Fikri Himawan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The holding of simultaneous elections on 17 April 2019 was the first time holding elections in Indonesia that combined presidential and legislative elections. The holding of simultaneous elections is an implication of the Constitutional Court Decision Number 14/PUU-XI/2013 in the case of reviewing Law Number 42 of 2008 concerning the General Election of the President and Vice President. Simultaneous elections are an effort to strengthen the presidential system. The research method used in this paper is normative juridical, which is defined as a procedural scientific research in order to find facts based on the scientific logic of law. The results of this study show that there is a positive trend towards holding simultaneous elections, namely increasing citizen participation to elect their leaders. In addition to the resulting positive trend, simultaneous elections also have drawbacks. The deficiency in question is the large number of sick and even death victims that occur in KPPS members. There are two causes of this incident including 1). The transition to the implementation of the electoral system which results in the addition of the work duties of KPPS members, 2). There was fraud in the recruitment of KPPS members which resulted in integrity and professionalism, so that KPPS members felt worried and stressed which had an impact on decreasing body health.